Atmospheric Response for MeV γ Rays Observed with Balloon-borne Detectors - Christopher M. Karwin; Carolyn Kierans; Albert Y. Shih; Israel Martinez Castellanos; Alex Lowell; Thomas Siegert; Jarred Roberts; Savitri Gallego; Adrien Laviron; Andreas Zoglauer; John A. Tomsick; Steven E. Boggs; et al. (The Astrophysical Journal)
The atmospheric response for MeV γ rays (∼0.1–10 MeV) can be characterized in terms of two observed components. The first component is due to photons that reach the detector without scattering. The second component is due to photons that reach the detector after scattering one or more times. While the former can be determined in a straightforward manner, the latter is much more complex to quantify, as it requires tracking the transport of all source photons that are incident on Earth’s atmosphere. The scattered component can cause a significant energy-dependent distortion in the measured spectrum, which is important to account for when making balloon-borne observations. In this work, we simulate the full response for γ -ray transport in the atmosphere. We find that the scattered component becomes increasingly more significant toward lower energies, and at 0.1 MeV, it may increase the measured flux by as much as a factor of ∼2–4, depending on the photon index and off-axis angle of the source. This is particularly important for diffuse sources, whereas the effect from scattering can be significantly reduced for point sources observed with an imaging telescope.